Lebensunwertes Leben: Roots and Memory of Aktion T4 - Silvestri, Erika (Conatus - Journal of Philosophy, 2019)
What the Nazis called Aktion T4 was a euthanasia program, officially started on August 18th, 1939. The registration operations for individuals with physical or mental handicaps were followed by forced sterilization and transfer to clinics organized to kill. In this article, I try to explain the mechanisms that allowed the memory of Aktion T4 to be preserved and passed from one generation to the next; memories of the “merciful death” of approximately 70,000 “lives unworthy of life,” that find themselves embedded in family records and family history. In the first section, I summarize the discussion that resulted from the theories of Charles Darwin and Francis Galton. Even if those theories do not in any way allude to the consequences that we have witnessed decades after their publication, they started a debate about the value of life and the legitimacy of human intervention in the selection of hereditary character traits, as well as the concept of race and the different methods and forms of theories and eugenics that were later adopted in Europe and in the United States. In the case of Germany, translated into Rassenhygiene, those concepts flowed into the Nazi project of purification of the German people. Through interviews with families who had a relative interned in one of the program's clinics spread across the Reich territory between 1939 and 1945, I investigate the evolution and passage of memories stored within the family sphere, paying attention to the generational steps and processes of trauma. These stories are born from a complicated process of reconstructing these memories via interviews. Their recollections were full of painful silences and negations, similar to the thought process which led the victims to live in a condition that they could not understand, and separated them from the world before they were each made to face a solitary death, far from any contact with their families. The trauma that I analyze concerns actions that had been carried out by previous generations; in the majority of cases, younger generations were not aware of the destiny of their murdered relatives and therefore tried to rebuild the stories of people who they never had the opportunity to meet. I examine the problematic relationship of those being interviewed with the end-of-life issue and also the sense of guilt which is generated by the awareness of crimes that were committed. Aktion T4 was not a crime committed outside the national borders, nor a crime that extended beyond the private sphere to the “others.” Instead, it existed within the most central and intimate place of Nazi culture: the family.